Immunochromatographic strip test for rapid detection of nevirapine in plasma samples from human immunodeficiency virus-infected patients - Tim R. Cressey (2018)
We report a novel one-step immunochromatographic strip test for the rapid, qualitative detection of nevirapine in plasma samples from human immunodeficiency virus-infected patients. The sensitivity was 100% (95% confidence interval [95% CI], 97.8 to 100%), and the specificity was 99.5% (95% CI, 97.2 to 99.9%). The limit of detection was 25 ng/ml. Immunochromatographic strip tests are simple, rapid, and cheap assays that could greatly facilitate drug level monitoring in resource-limited settings. Copyright © 2007, American Society for Microbiology. All Rights Reserved.